Fibrillary glomerulonephritis: a rare entity with unique ultrastructural characteristics - Karanfilovski, Vlatko; Severova Andreevska, Galina; Dzekova Vidimliski, Pavlina (My University, 2022)
Fibrillary glomerulonephritis (FGn) is characterized by deposition of randomly arranged polyclonal immune deposits in glomerular matrix. A 56-year-old hypertensive patient presented to our hospital with proteinuria (3.04 g/24 hours) and an elevated serum level of creatinine (391 μmol/L). Electron microscopic evaluation of kidney biopsy specimens set the diagnosis of fibrillary glomerulonephritis (Figure 1). There was no evidence of monoclonal components in the blood and urine. Antinuclear and anti-double-stranded DNA antibodies, complement components C3 and C4, and markers of viral hepatitis were also negative. The benefit of immunosuppressants is limited, and half of patients progress to kidney failure within 2 years.